2021
DOI: 10.1021/acsapm.1c01267
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Na-Ion Conducting Polymer Gel Membrane for Supercapacitor Applications

Abstract: The scarcity of Li along with its uneven distribution in earth has become a great challenge in the field of electrochemical energy storage. Replacing Li with Na may address the above issues, as Na and Li are very similar in electrochemical characteristics, and Na is abundant in nature with low cost. Herein, the Na-ion conducting gel polymer membranes comprising a 2-HEC/EMITf/NaTf system are synthesized by employing the solution-casting method. The effects of NaTf salt and EMITf ionic liquid on the electrical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Pure polymer shows a broad peak around 2θ = 20.8 , which describes its semicrystalline nature due to the hydrogen bonds within the polymer chains. 18,19 The change in the intensity and breadth of this XRD broad peak confirms the change in the crystallinity. It is evi- In order to understand the variation in the crystallinity, XRD spectra deconvolution has been performed using the Gaussian fitting function using Fityk open-source software to reveal amorphous and crystalline peaks.…”
Section: Xrd Studiesmentioning
confidence: 53%
See 2 more Smart Citations
“…Pure polymer shows a broad peak around 2θ = 20.8 , which describes its semicrystalline nature due to the hydrogen bonds within the polymer chains. 18,19 The change in the intensity and breadth of this XRD broad peak confirms the change in the crystallinity. It is evi- In order to understand the variation in the crystallinity, XRD spectra deconvolution has been performed using the Gaussian fitting function using Fityk open-source software to reveal amorphous and crystalline peaks.…”
Section: Xrd Studiesmentioning
confidence: 53%
“…Pure polymer shows a broad peak around 2𝜃 = 20.8°, which describes its semicrystalline nature due to the hydrogen bonds within the polymer chains 18,19 . The change in the intensity and breadth of this XRD broad peak confirms the change in the crystallinity.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…In general, electrolyte is the most important aspect of energy storage technology because it functions as a bridge between the electrodes, allowing ions to pass between them and improving the overall performance such as electrochemical potential window, long-term cycling, C-rates, etc. Hence, an effectively designed electrolyte is required for the battery applications in order to achieve a high-performance energy device. , …”
Section: Introductionmentioning
confidence: 99%
“…Along with the increasing global demands for clean and safe renewable energy resources, there is an increasing demand to develop sustainable and environmentally friendly energy storage devices. Supercapacitors (double capacitors and pseudocapacitors), as a type of energy storage device, have attracted extensive attention from scientists because of the unique features of high power density, long cycle life, fast charge–discharge characteristics, and environmental friendliness. The conductive polymer is a type of ideal electrochemically active material for electrodes due to its excellent biocompatibility, favorable electrical properties, environmental stability, and reliable electrochemical stability. Polypyrrole (PPy), one of the most typical conducting polymers, which is easy to synthesize, , has excellent conductivity (in the doped state), good environmental stability, good biocompatibility, relatively low cost, , and good redox reversibility. ,, However, the poor specific capacity of PPy particles limited their deeper development in high-performance supercapacitors. It was reported that the nanostructure and morphology of electrode materials have an important impact on their electrochemical energy storage properties .…”
Section: Introductionmentioning
confidence: 99%